Indium(III)-Catalyzed One-Pot Synthesis of Alkyl Cyanides from Carboxylic Acids - Moriya, Toshimitsu; Shoji, Kohei; Yoneda, Shinichiro; Ikeda, Reiko; Konakahara, Takeo; Sakai, Norio (Synthesis, 2013)
The one-pot preparation of alkyl cyanides from carboxylic acids via alkyl iodides or alkyl bromides, which were in situ generated either by indium(III)-catalyzed reductive iodination or bromination of carboxylic acids, is described.
Keywords: indium; deoxygenation; halogenation; carboxylic acids; nitriles